The Study of Post-Earthquake Livelihood Strategy in Tandikek Padang Pariaman District - Sosmiarti Syafruddin Karimi Melinda Noer, Werry Darta Taifur (Universitas Andalas, 2018)
The objective of this study is to investigate life asset condition and household life recovery strategy after and before earthquakes in Tandikek, Padang Pariaman District. Livelihood index assessment is used to describe livelihood asset changes before and after the earthquake. A descriptive analysis is employed to describe life recovery strategy that is used by households in various level and phase of house damages. The result of the study shows that change in household life asset after the earthquake has U pattern, meaning that condition of assets for all indicators decreased during emergency and recovery phases. This condition, however, increased after recovery phase up to the present time. The condition is even better than that prior to the earthquake. This also means that all recovery efforts have successfully developed people’s life assets that guarantee their life after the earthquake. The livelihood recovery strategy used by households in Tandikek to maintain and recover their livelihood varies according to the level and phase of the house damage. The households that take independent livelihood strategy, either in active or passive way, networking strategy and utilization of disaster aids from various sources appear to recover faster than those who only take one strategy.